Biological response modifier therapy for refractory childhood uveitis. Issue 10 (7th June 2007) - Gallagher, Michael; Quinones, Karina; Cervantes-Castañeda, Rene Antonio; Yilmaz, Taygan; Foster, C Stephen
Abstract : Purpose: To evaluate the use of biological response modifiers (BRM) in the treatment of refractory childhood uveitis. Design: Retrospective non-comparative case series of pediatric patients with uveitis treated with BRM. Participants: 23 pediatric patients. Methods: All children (18 years or younger) who received a BRM were assessed for visual changes, time to control inflammation, and any associated adverse side effects. Thirteen patients were treated with infliximab, five with adalimumab, and five with daclizumab. All patients had bilateral eye involvement. Diagnoses of the participants included juvenile idiopathic arthritis, keratouveitis, sarcoid panuveitis, Adamantiades–Behcets disease, and idiopathic panuveitis. Main outcome measures: Inflammation and visual acuity. Results: In the infliximab group 16 of 26 eyes (62%), and 10 of 13 patients (77%) demonstrated an improvement in visual acuity. Twenty of 26 eyes (77%) demonstrated an improvement in the degree of inflammation. In the adalimumab group, four of 10 eyes (40%) demonstrated an improvement in visual acuity, with five of 10 eyes (50%) demonstrating an improvement in inflammation. Four of 10 eyes (40%) in the daclizumab group demonstrated an improvement in vision with eight of 10 eyes (80%) demonstrating an improvement in inflammation. Conclusion: BRM appear to be safe to use in children, and represent a useful therapeutic adjunctive drug group for treating recalcitrant childhood uveitides.